2010
DOI: 10.1186/1471-2164-11-707
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide SNPs and re-sequencing of growth habit and inflorescence genes in barley: implications for association mapping in germplasm arrays varying in size and structure

Abstract: BackgroundConsiderations in applying association mapping (AM) to plant breeding are population structure and size: not accounting for structure and/or using small populations can lead to elevated false-positive rates. The principal determinants of population structure in cultivated barley are growth habit and inflorescence type. Both are under complex genetic control: growth habit is controlled by the epistatic interactions of several genes. For inflorescence type, multiple loss-of-function alleles in one gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
67
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(80 citation statements)
references
References 52 publications
11
67
0
1
Order By: Relevance
“…The significant marker on 4H maps to the reported position of the INTERMEDIUM-C (Int-c) gene (Cuesta-Marcos et al, 2010) that influences both fertility of lateral spikelets on the inflorescence and amount of basal branching (tillering) in barley (Ramsay et al, 2011). The one significant marker on chromosome 5H is most likely detecting the six-rowed spike 2 (vrs2) or the intermedium spike-b (int-b) locus (Cuesta-Marcos et al, 2010). Some or all of the unmapped SNPs are likely located near or at vrs1, vrs2, int-b, Int-c or some other spike morphology genes described on chromosome 1H (Cuesta-Marcos et al, 2010).…”
Section: Genome-wide Association Mapping Of Barley Spike Morphologymentioning
confidence: 99%
“…The significant marker on 4H maps to the reported position of the INTERMEDIUM-C (Int-c) gene (Cuesta-Marcos et al, 2010) that influences both fertility of lateral spikelets on the inflorescence and amount of basal branching (tillering) in barley (Ramsay et al, 2011). The one significant marker on chromosome 5H is most likely detecting the six-rowed spike 2 (vrs2) or the intermedium spike-b (int-b) locus (Cuesta-Marcos et al, 2010). Some or all of the unmapped SNPs are likely located near or at vrs1, vrs2, int-b, Int-c or some other spike morphology genes described on chromosome 1H (Cuesta-Marcos et al, 2010).…”
Section: Genome-wide Association Mapping Of Barley Spike Morphologymentioning
confidence: 99%
“…Among various types of DNA markers, microsatellites (SSR) and single nucleotide polymorphism (SNP) have been widely used for genome analyses (Cockram et al 2010; Cuesta-Marcos et al 2010; Honsdorf et al 2014; Varshney et al 2007). The first high-density gene map based on SNP markers contained 2.943 SNP loci in 975 marker bins and covered a genetic distance of 1099 cM (Close et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The analysis uncoupled FHB resistance from head phenotype (two rows vs six rows, Cuesta-Marcos et al 2010) and identified novel alleles for the known and robust FHB QTL and provided a good example for the broad integration of technologies. Progressive use of Genome Wide Association Studies (GWAS, Berger et al 2013; Cuesta-Marco et al 2010) expands the database of molecular information linked to phenotype and THT provides a valuable model for translating these data to industry.…”
Section: Translation Of Genomics To Industry and Modifying Specific Tmentioning
confidence: 99%